Applying water footprint assessment with the aim of achieving sustainable water resource management at a large commercial beef cattle feedlot in Gauteng Province - Pearce, Lisa (Department of Environmental and Geographical Science, 2017)
The commercial production of beef meat is associated with a wide array of environmental impacts, and is itself very sensitive to environmental conditions. Water in particular is a critical environmental resource and the commercial success of an agri-business is closely tied to reliance on fresh water resources. In an economic sector that is increasingly faced with competition for resources as well as negative public opinion about environmental impacts, the management of water-related risks and impacts is essential to ensure business resilience and sustainability. Global trends in animal production are causing the environmental problems to become more harmful, and intensive animal production is being separated from traditional crop farming systems where manure could be used as a fertilizer to replenish soil nutrients. There is a spatial disconnect in the production value chain brought about by commercial trends. An on-site water efficiency approach to water resources management of an agri-business does not enable it to evaluate value chain water-related risks, or its' own contribution to sustainable water use in the catchments where raw materials are produced and production wastes are distributed. The question of sustainable water use within the production value chain of beef meat is not solved with an on-site efficiency approach to water resources management because the approach is inadequate in evaluating the freshwater environmental impact, or in managing water-related business risks of the whole beef production value chain. It is argued that a systems approach is more credible because it allows a beef cattle feedlot enterprise to evaluate freshwater impacts across the production value chain and will enable a feedlot to transition towards a sustainable value chain water resources management model The Water Footprint of food, goods and services is a volumetric expression of the water that is consumed during the production process. Unlike water use, the water footprint refers to water that is imbedded into a product (also referred to as virtual water) or otherwise made unavailable for further use within a catchment, province or country through pollution dilution. The Water Footprint Network developed the Water Footprint Assessment and describes three types of WF: the green water footprint refers to evaporated water, typically in the form of rainwater. The blue water footprint refers to water that is abstracted from a resource and delivered to the point of use, for example in the case of irrigation from a river, borehole or dam. The grey water footprint is a volumetric expression of the amount of fresh water required to dilute chemical substances to a safe or acceptable concentration in the natural environment. A Water Footprint Assessment (WFA) was undertaken at a beef cattle feedlot in Gauteng, South Africa. The WFA focused on the Bovine WF of the 4-month winter- and summer finishing periods that cattle spend at the feedlot. The second focus was on the monthly grey WF of waste management activities at the feedlot. The purpose of the study was to determine how the application of a WFA would enable an agri-business to transition from an on-site approach to water resources management, to a value-chain systems approach to sustainable water resource management.